2020
DOI: 10.11650/tjm/200102
|View full text |Cite
|
Sign up to set email alerts
|

The Monochromatic Connectivity of Graphs

Abstract: In 2011, Caro et al. introduced the monochromatic connection of graphs. An edge-coloring of a connected graph G is called a monochromatically connecting (MC-coloring, for short) if there is a monochromatic path joining any two vertices. The monochromatic connection number mc(G) of a graph G is the maximum integer k such that there is a k-edge-coloring, which is an MC-coloring of G. Clearly, a monochromatic spanning tree can monochromatically connect any two vertices. So for a graph G of order n and size m, mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In [8,9], the authors generalized the concept of MC-coloring. For more knowledge about the monochromatic connection of graphs, we refer to [1,3,5,6,10,11]. In [4], Caro and Yuster showed that the bound of the second result is sharp, and they studied wheel graphs, outerplanar graphs and planar graphs with minimum degree three.…”
Section: Theorem 12 ([4]mentioning
confidence: 99%
“…In [8,9], the authors generalized the concept of MC-coloring. For more knowledge about the monochromatic connection of graphs, we refer to [1,3,5,6,10,11]. In [4], Caro and Yuster showed that the bound of the second result is sharp, and they studied wheel graphs, outerplanar graphs and planar graphs with minimum degree three.…”
Section: Theorem 12 ([4]mentioning
confidence: 99%
“…The notion monochromatic vertex-connection coloring was introduced by Cai, Li and Wu [5] in 2018, which is defined from the vertex-version. For more results on the monochromatic connection coloring and vertex-connection coloring, we refer to [4,6,8,14].…”
Section: Introductionmentioning
confidence: 99%
“…[18] Let G be a connected graph of order n ≥ 7. If G does not have subgraphs isomorphic to K − 4 , then mc(G) = m − n + 2, where K − 4 denotes the graph obtained from K 4 by deleting an edge.Theorem 2.3.…”
mentioning
confidence: 99%
“…[18] Let G be a connected graph of order n ≥ 7. If G does not have two vertex-disjoint triangles, then mc(G) = m − n + 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation